Produção de oligossacarídeos pre-bióticos em suco de frutas - Fontes, Claudia Patrícia Mourão Lima (2013)
Nowadays, people have been concerned with their quality of life and wellness,increasing the consumption of foods, with prebiotic oligosaccharides, which may improve the health and decrease the disease risks. In recent years, a lot of new foods have been developed with these compounds (prebiotic oligosaccharides)including the fruit juices. The aim of this work was the prebiotic oligosaccharides production in orange, pineapple and melon juices, and their spray drying.The dextransucrase, produced by L. mesenteroides NRRL B-512F, was used for enzymatic synthesis following a central composite experimental design, with sucrose and reducing sugars variation, at 30 °C/ 24h. The prebiotic juices obtained were dried by spray drying, varying the maltodextrin and arabic gum concentration (10 and 20%) and the inlet temperatures (160 and 180 °C). Pineapple, orange and melon juices showed better results when maltodextrin(20%) and the inlet temperature 180 °C were utilized. The juice powders obtained showed low water activity, moisture,higroscopicity and rehydration time. These results give better microbiology and physicochemical stability, as well as, fast preparation. There was a decrease of the antioxidant activity at all products. The fruit juices used demonstrated an excellent way to produce, by enzymatic synthesis, prebiotic oligosaccharides with high polymerization degrees.